Obeticholic acid improved triptolide/lipopolysaccharide‐induced hepatotoxicity by inhibiting caspase‐11‐GSDMD pyroptosis pathway. Issue 4 (9th November 2022) - Liang, Peishi; Zhou, Shaoyun; Yuan, Ziqiao; Zhang, Luyong; Jiang, Zhenzhou; Yu, Qinwei
Abstract: This study was designed to investigate the potential role of farnesoid X receptor (FXR) in abnormal bile acid metabolism and pyroptosis during the pathogenesis of triptolide (TP)/lipopolysaccharide (LPS)‐induced hepatotoxicity. Moreover, the protective effect of obeticholic acid (OCA) was explored under this condition. In vivo, female C57BL/6 mice were administrated with OCA (40 mg/kg bw, intragastrical injection) before (500 μg/kg bw, intragastrical injection)/LPS (0.1 mg/kg bw, intraperitoneal injection) administration. In vitro, AML12 cells were treated with TP (50 nM) and TNF‐α (50 ng/ml) to induce hepatotoxicity; GW4064 (5 μM) and cholestyramine (CHO) (0.1 mg/ml and 0.05 mg/ml) were introduced to explain the role of FXR/total bile acid (TBA) in it. Serum TBA level was significantly elevated, which was induced by FXR suppression. And both GW4064 and CHO intervention presented remarkable protective effects against TP/TNF‐α‐induced NLRP3 upregulation and pyroptosis pathway activation. Pre‐administration of FXR agonist OCA successfully attenuated TP/LPS‐induced severe liver injury by reducing serum bile acids accumulation and inhibiting the activation of caspase‐11‐GSDMD (gasdermin D) pyroptosis pathway. We have drawn conclusions that TP aggravated liver hypersensitivity to LPS and inhibited FXR‐SHP (small heterodimer partner) axis, which was served as endogenous signals to activate caspase‐11‐GSDMD‐mediated pyroptosis contributing to liver injury. OCA alleviated TP/LPS‐induced liver injury accompanied by inhibiting caspase‐11‐GSDMD‐mediated pyroptosis pathway and decreased serum TBA level. The results indicated that FXR might be an attractive therapeutic target for TP/LPS‐induced hepatotoxicity, providing an effective strategy for drug‐induced liver injury. Abstract : Accordingly, triptolide (TP) aggravated liver hypersensitivity to lipopolysaccharide (LPS)‐induced hepatotoxicity, but there is no treatment strategy for it so far. The study aims to investigate the effect and mechanism of obeticholic (OCA) on TP/LPS‐induced hepatotoxicity. It has been found that OCA protected TP/LPS‐induced hepatotoxicity by inhibiting caspase‐11‐GSDMD pyroptosis pathway. And both reduction of bile acids and inhibition of FXR could improve TP/LPS‐induced pyroptosis. The results demonstrated that OCA might be a potential therapeutic drug for TP/LPS‐induced hepatotoxicity.